Strategic investment decision-making: communicating the true meaning of the real options framework to the board - Monmans, Lisette; Leoni, Peter; Mercken, Roger; Houben, Ghislain (Uniwersytet Ekonomiczny we Wrocławiu, 2010)
Once heralded as a revolution in capital budgeting and enthusiastically put forward as a major breakthrough to explore the real value of strategic investment projects, the real options approach seems to be losing momentum. For many senior managers and members of board of directors, ‘real options’ is nothing more than a theoretical-academic construct that is hard to apply in practice. Decision analysis, the multiperiod binomial model and the Black-Scholes and Margrabe formulae are well known but sometimes poorly applied and distrusted. Taking strategic investment opportunities as real options is widely accepted as the right approach, but the mathematical models to evaluate those options are often not understood. For that reason we believe that there still is a need to better communicate the true meaning of real options and of options thinking to senior management and board of directors. The setup of a gradually developing line of communication with the board is illustrated by means of simplified but real applications of the concepts.
Argumenta Oeconomica, 2010, Nr 2 (25), s. 137-162
Keywords: Black-Scholes model; multiperiod binomial model; Margrabe formula; real options; decision analysis